Coseismic Displacement and Slip Distribution of the 21 May 2021 Mw 6.1 Earthquake in Yangbi, China Derived From InSAR Observations - Li, Yongsheng; Li, Yujiang; Liang, Kuan; Li, Hao; Jiang, Wenliang (Frontiers in Environmental Science, 2022)
On May 21, 2021, a Mw 6.1 earthquake struck Yangbi County, Yunnan Province, China. In this study, InSAR data from Sentinel-1 SAR images were processed to image the coseismic deformation fields of the Yangbi earthquake. Then, the optimal slip model was obtained by applying the particle swarm optimization method. The interferometry results revealed that the earthquake triggered obvious surface deformation near the epicenter, while the earthquake did not produce an obvious surface rupture zone from field investigation. The optimal slip model suggests that the strike of the seismogenic fault responsible for this event is 139°, the dip angle is 81°, and the average rake angle is -170°. Additionally, the slip was concentrated mainly at depths of 2–8 km, the maximum dip-slip amount was 0.5 m, and the cumulative seismic moment reached 1.43×1018 Nm, equivalent to a Mw 6.1 earthquake. The geodetic and geophysical inversion results demonstrate that the Yangbi earthquake was dominated by a steeply dipping dextral strike-slip rupture. The rupture fault generally strikes NNW-SSE, which is consistent with that of the Weixi-Qiaohou fault, and may be a relatively new fault formed by an E-W-oriented extension of the western boundary of the Sichuan-Yunnan block. Finally, based on the InSAR results in combination with the spatial distribution characteristics of ground fissures and the strong historical earthquakes, we analyzed the tectonic background preceding the Yangbi earthquake and analyzed the relationship between the Yangbi earthquake and strong historical earthquakes in the region, thereby providing empirical evidence for analyzing seismic risk and fault rupture parameters, interpreting seismic deformation characteristics, and better understanding the seismogenic background of the western boundary of the Sichuan-Yunnan block.